Explaining rising regionalism and failing multilateralism: Consensus decision-making and expanding WTO membership - Euan MacMillan (University College Dublin, UCD School of Economics, 2009)
The beleaguered progress of the Doha Development Agenda of the WTO presents something of a puzzle for economic theory: if multilateralism is an effective forum for liberalisation (as it has been in the past), then why have the current round of talks faltered amid the proliferation of preferential trade negotiations? Several authors have argued that the consensus decision-making and single-undertaking principles of the WTO have lead to coordination failures amongst an increasingly expanded and diverse membership which has caused frustrated WTO members to form PTAs. This paper constructs a formal model which shows that the combination of the single-undertaking and consensus decision-making principles with an expanded and more diverse membership can lead to more than just coordination failure; it can render multilateralism less desirable for some parties than bilateralism. It is argued that these principles give countries de facto veto power meaning that their threat point during multilateral negotiations is a reversion to bilateral negotiations between all parties. Accordingly, countries with relatively less to gain from multilateralism can use their veto power to extract gains from those that would benefit substantially from the WTO. If an expanding membership has increased the number of such countries, then the benefits of multilateralism versus regionalism from the perspective of their negotiating partners may have been diminished to such an extent that they are no longer willing to wait for the conclusion of the Doha round before engaging in regional negotiations. This result adds credence to the idea that variable geometry be introduced into the WTO system, such that it acts as an umbrella organisation for a web of sub-agreements.
hdl:10197/2619
Keywords: 330